Pediatric Brain Tumors: Surgical Approaches and Long-Term Neurocognitive Outcomes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
With an incidence in around 3/100,000 children, pediatric brain tumors represent the most frequent hard tumors that cause morbidity and mortality in children worldwide. The objective of this study is to evaluate the role of surgical techniques in the treatment of pediatric brain tumors, to assess health-related quality of life, and to determine neurocognitive outcomes. A comprehensive data set encompassing demographic and clinical parameters was meticulously collected from 120 pediatric patients diagnosed with brain tumors across multiple hospitals in Basrah, Iraq. The study's inclusion criteria were limited to patients aged 2–16 years. The patient data were obtained from the hospitals, including demographics (age, sex, BMI, etc.), diagnostics (tumor location and type), and surgical outcomes. Complications and pain experienced by the patients were meticulously documented, and quality-of-life assessments were conducted using the SF-36 questionnaire. The present study enrolled clinical outcomes of 120 samples of pediatric brain tumors. The analysis revealed that the most prevalent clinical outcomes were headache (43.33%) and nausea/vomiting (25%), with tumor location in the posterior fossa (41.67%) and parietal bone (20.83%) being significant. The surgical approach was predominantly elective (88.33%), indicating a preference for surgical intervention. All patients underwent surgical resection in different hospitals during follow-up. Post-surgical complications occurred in 65% of patients, neurological complications in 22.5%, surgical site infections in 14.17%, and mortality in 13.33%. Surgical resection is the most common procedure for acute cases of pediatric brain tumors in terms of mortality rates and quality of life complications.